Symposium: Driving Black Student Success on a System-Wide Level - Murray, Karen; West-Burns, Nicole; De Jesus, Stephanie; Armson, Sarah; Cameron, David H.; Kapoor, Aakriti; James, Carl; Anane-Bediakoh, Beatrice (Journal of the Canadian Association for Curriculum Studies, 2020)
Qualitative and quantitative data indicators from the Toronto District School Board (TDSB) and York University highlight the crucial need for a holistic Black Student Success and Excellence (BSSE) strategy to address systemic racism that Black students face in all aspects of their schooling. To this end, TDSB developed a program to foster critical consciousness in educators. The initiative partnered educators, school administrators, central support staff, associated researchers and initiative leaders in an inquiry-based journey relevant to their role(s), space(s) and experience. The study took place in 17 secondary and elementary schools. Results demonstrate that participants fostered their own critical consciousness and that of their students’ through the research or inquiry process. The symposium details experiences from across this work. It also explores the direct and indirect effects of the initiative on participants related to the conditions and mechanisms for entry, implementation, mobilization and sustainability, and processes within the initiative at micro and macro levels. As an extension of this work, TDSB and York University also piloted a Black Student Summer Leadership Institute to provide Black secondary students with opportunities to understand and develop leadership and agency in challenging anti-Black racism through principles of Youth Participatory Action Research. As part of their inquiry, students in the summer program also identified the following key themes to describe the Black student experience: sense of belonging, stress, engagement, body/self-image, neglect, student voice and safety. Overall, this panel highlights the different components, challenges and successes with this initiative and implications for expanding this work.